Treatment and posttreatment outcomes induced by the Mandibular Advancement Repositioning Appliance; A controlled clinical study - Ghislanzoni, Luis Tomas Huanca; Toll, Douglas Edward; Defraia, Efisio; Baccetti, Tiziano; Franchi, Lorenzo (The Angle orthodontist, 2011)
To evaluate the treatment and posttreatment dentoskeletal effects induced by the Mandibular Advancement Repositioning Appliance (MARA) in the treatment of Class II malocclusion. The treated sample consisted of 23 consecutively treated patients at prepubertal or pubertal stages, as assessed by the cervical vertebral maturation method. A control group of untreated Class II subjects was generated from published normative growth data. Lateral cephalograms were digitized and superimposed via cephalometric software at three different times: T1, pretreatment; T2, post-MARA treatment; and T3, at least 1 year after T2. The T1-T2, T2-T3, and T1-T3 changes in the treated group were compared to those in the control group with independent-sample Student's t-tests. Skeletal and dentoalveolar effects of MARA were assessed after the active phase of the treatment (T1-T2). Mandibular elongation in length (Co-Gn, +2.2 mm) was evident together with lower incisor proclination (IMPA, +5.8 mm). A relapse tendency for IMPA was noticed after removing the appliance (IMPA, -2.1° during T2-T3). Significant skeletal effects (Co-Gn, +2.0 mm) and headgear effects on the maxilla (SNA, -1.2°) were significant in the long term (T1-T3). The MARA appliance provides an effective correction of Class II malocclusion, which is maintained at a posttreatment observation with a moderate skeletal effect.